The Influence of Organization Culture and Work Environment toward Work Motivation which Implications for The Job Performance The Charitable Efforts of Muhammadiyah Education Institutions in Tangerang-Indonesia - Muh. Abdul Rosid; Lena Endarwati; Indah Kusumawati (Formosa Journal of Science and Technology, 2022)
The purpose of this study was to determine the influence of organizational culture, work environment and work motivation toward job performance in the charitable efforts of Muhammadiyah education institutions in Tangerang city. The study resulted in: 1). organizational culture was significantly (positively) correlated with work motivation by 16.5%, 2). work environment was significantly (positively) correlated with work motivation by 82.7%, 3). organizational cultures and work environment were significantly (positively) correlated with work motivation by 95.7%, 4). organizational cultures was significantly (positively) correlated with job performance by 26.6%, 5). work environment was significantly (positively) correlated with job performance by 61.2%, 6). work motivation was significantly (positively) correlated with job performance by 26.6%, 7). organizational cultures, work environment and work motivation were significantly (positively) correlated with job performance by 95.2%.